1999
DOI: 10.1046/j.1365-313x.1999.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Three 4‐coumarate:coenzyme A ligases in Arabidopsis thaliana represent two evolutionarily divergent classes in angiosperms

Abstract: SummaryThe enzyme 4-coumarate:CoA ligase (4CL) plays a key role in channelling carbon¯ow into diverse branch pathways of phenylpropanoid metabolism which serve important functions in plant growth and adaptation to environmental perturbations. Here we report on the cloning of the 4CL gene family from Arabidopsis thaliana and demonstrate that its three members, At4CL1, At4CL2 and At4CL3, encode isozymes with distinct substrate preference and speci®cities. Expression studies revealed a differential behaviour of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
478
2
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 402 publications
(520 citation statements)
references
References 41 publications
35
478
2
5
Order By: Relevance
“…Further kinetic analysis revealed that Pt4CL1 activated CA and PA with similar catalytic efficiency (V max /K m ; Table I). This is consistent with characteristics of lignin-related 4CLs in other species with multiple, kinetically distinct isoforms (Knobloch and Hahlbrock, 1975;Ehlting et al, 1999). Pt4CL2 exhibited a much higher catalytic efficiency for PA than for CA, due primarily to a very low K m for PA (Table I).…”
Section: Kinetic Analysis Of Recombinant Aspen 4cl Proteinssupporting
confidence: 82%
See 4 more Smart Citations
“…Further kinetic analysis revealed that Pt4CL1 activated CA and PA with similar catalytic efficiency (V max /K m ; Table I). This is consistent with characteristics of lignin-related 4CLs in other species with multiple, kinetically distinct isoforms (Knobloch and Hahlbrock, 1975;Ehlting et al, 1999). Pt4CL2 exhibited a much higher catalytic efficiency for PA than for CA, due primarily to a very low K m for PA (Table I).…”
Section: Kinetic Analysis Of Recombinant Aspen 4cl Proteinssupporting
confidence: 82%
“…Wounding, UV light, and elicitors increase transcript abundance of different 4CL isoforms (Uhlmann and Ebel, 1993;Ehlting et al, 1999), reinforcing the model that there are distinct associations between isoforms and specific metabolic activities. However, all 4CLs subjected to in vitro kinetic analysis so far exhibit similar broad substrate specificity, generally favoring PA, followed by FA and CA (Ranjeva et al, 1976;Grand et al, 1983;Uhlmann and Ebel, 1993;Hu et al, 1998;Ehlting et al, 1999). Site-directed mutagenesis has recently been applied to elucidate the mechanism and evolution of 4CL catalysis (Stuible et al, 2000).…”
supporting
confidence: 58%
See 3 more Smart Citations